Parametric differences in L1 gender assignment systems and implications for French L2 assignment mastery - Pieters, Tatiana (Círculo de Lingüística Aplicada a la Comunicación, 2018)
The present study examines cross-linguistic influences of L1 German and L1 English grammatical gender (GG) systems on GG mastery in French L2. It compares oral production data by two different learner groups of French and a francophone control group. The L1’s have been selected on the bases of the nature of their gender assignment systems (AS), which differ from the French system according to macro and micro parameters, that is the number of distinguished gender values and the different assignment criteria at hand (Corbett 1991). The study posits as a starting point that these L1 parametric differences affect assignment performances in FL2. The results indicate firstly that performances on gender assignment are higher among learners whose L1 AS shows the least parametric asymmetries with the French system. Secondly, learners whose L1 does not operate GG are more likely to overassign the masculine gender.